2022
DOI: 10.1038/s41598-022-15271-x
|View full text |Cite|
|
Sign up to set email alerts
|

Statistical evaluation of proxies for estimating the rainfall erosivity factor

Abstract: Considering the high-temporal-resolution rainfall data requirements for calculating the Rainfall Erosivity factor (that is, the R-factor), studies have developed a large number of proxies for the R-factor (PR). This study aims to evaluate 15 widely used proxies, which were developed in various countries using daily, monthly, or yearly rainfall data, in terms of correlation and statistical equality with the R-factor by using the 6-min pluviographic data from 28 stations in Australia. Meng’s test was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The utilisation of the MFI has been recommended by several authors as a reliable index for the assessment of the potential of the precipitation to generate erosion. The authors in [38,45] found a significant correlation between the MFI and the rainfall erosivity factor (R) in the universal soil loss equation (USLE).…”
Section: Methodsmentioning
confidence: 99%
“…The utilisation of the MFI has been recommended by several authors as a reliable index for the assessment of the potential of the precipitation to generate erosion. The authors in [38,45] found a significant correlation between the MFI and the rainfall erosivity factor (R) in the universal soil loss equation (USLE).…”
Section: Methodsmentioning
confidence: 99%